2021
DOI: 10.1016/j.jtcme.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease: Effects of ethanolic extracts of seed kernels of mango (Mangifera indica .L) on acute hind limb ischemia-reperfusion injury in diabetic rats

Abstract: Background and aim Hind limb ischemia is one of the peripheral arterial diseases affecting majority of the people with atherosclerosis, diabetes and chronic cigarette smokers. Hind limb ischemic-reperfusion injury is also one of the exacerbating events in these peoples, resulting in hind limb dysfunction. The aim of this study was to identify the effects of ethanolic extracts of mangifera indica (EEMI) on reversing hind limb dysfunction in diabetic rats with acute hind l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…Increased oxidative stress is the characteristic feature of endothelial cell dysfunction and vascular pathology both in human and animals (Huang 2009 ), and it is also induced by unregulated high glucose levels (Whiting et al 2008 ). Diabetes and ischemia-induced the accumulation of ROS mediated endothelial cell death and decreased anti-oxidant enzyme level which is required for GSH synthesis (RamPravinKumar et al 2021 ), and the above phenomena were confirmed in our in vivo and in vitro studies. The depletion of AURKA could promote ROS production thereby inducing cell apoptosis (Wang et al 2016 ), suggesting its potential anti-oxidant effect in diabetic limb ischemia.…”
Section: Discussionsupporting
confidence: 83%
“…Increased oxidative stress is the characteristic feature of endothelial cell dysfunction and vascular pathology both in human and animals (Huang 2009 ), and it is also induced by unregulated high glucose levels (Whiting et al 2008 ). Diabetes and ischemia-induced the accumulation of ROS mediated endothelial cell death and decreased anti-oxidant enzyme level which is required for GSH synthesis (RamPravinKumar et al 2021 ), and the above phenomena were confirmed in our in vivo and in vitro studies. The depletion of AURKA could promote ROS production thereby inducing cell apoptosis (Wang et al 2016 ), suggesting its potential anti-oxidant effect in diabetic limb ischemia.…”
Section: Discussionsupporting
confidence: 83%
“…An extract of Mangifera indica administered to LDL-receptor-deficient mice for 2 weeks produced a reduction in plasma and liver cholesterol levels, ROS production in spleen mononuclear cells and increased plasma total antioxidant capacity [ 146 ]. Mangiferin activity in PAD was also indirectly investigated using ethanolic extracts of mango seed (EEMI) in an acute hindlimb ischemia-reperfusion model [ 147 ]. Streptozotocin-treated diabetic rats underwent a femoral artery ligation and, then, received EEMI (0.2–0.4 g/kg) for 14 days.…”
Section: Specific Polyphenolic Compounds Of Interestmentioning
confidence: 99%
“…Blood flow was observed to be significantly higher in treated animals than in the controls. The plasma levels of malondialdehyde, IL–6, TNF–α and IL–1β were reduced, while glutathione and IL–10 levels were increased in EEMI-treated animals, suggesting anti-inflammatory modulation [ 147 ]. In general, given the above reported experimental data, mangiferin appears to offer promise in the prevention and treatment of vascular disease also linked to diabetes and dyslipidemia.…”
Section: Specific Polyphenolic Compounds Of Interestmentioning
confidence: 99%
“…The kernel contained in the seeds (mango seed kernel: MSK) is a good source of carbohydrates (58-80%), contains moderate amounts of protein (6-13%), and has a fat content (6-16%) [15]. Meanwhile, a study of mango seeds in the area of medicine found that mango seeds are a by-product that is usually discarded even though they are identified as a natural source of phenolic compounds with health-promoting activities as well as multifunctional bioactive ingredients for nutraceutical and cosmeceutical applications [20], [21], [22]. The effect of the ethanolic extract contained in mango seeds can restore tissue damage in acutely injured hind limb ischemia in diabetic rats [23].…”
Section: Introductionmentioning
confidence: 99%